RANCANG BANGUN PENGELOLAAN SAMPAH TERPADU ANTAR DAERAH BERBASIS PERMAINAN DINAMIS - Ika Nugraheni AM; Muhammad Wakhid Musthofa (Universitas Medan Area, 2019)
Joint waste management between regions that bordered each other can be one alternative solution of the problem of trash in Indonesia. Some areas have conducted cooperation in waste management, such as Sarbagita and Kartamantul. Dynamic game can be an alternative method in joint waste management between the regions. The purpose of this article is to design joint waste management between regions using the dynamic game theory framework approach. A dynamic game is a mathematical model that represents the conflict situation between the interested parties who want to make the best decision (in this case it is the city/district government) of a series of strategies that are possible by considering the existence of the various uncertainties at such situation. The discussion is done by assuming there are three areas of the bordering regoins and making some waste disposal regulations. Furthermore, the mathematical operations and simplification of the form of equation are executed to adapt to the design objectives. The results of the design in this approach are the invention of two mathematical equations describing the characteristics of dynamics waste stock in the adjoining regoins, and the cost to be incurred by each regions in managing its waste stock.